Pengaruh Model Pembelajaran IPA menggunakan Model Kooperatif Type Group Investigation Berbantuan Multimedia Pembelajaran terhadap Kemampuan Berpikir HOTS - Julianti, Elisa; Widi Winarni, Endang; Muktadir, Abdul (UNIB Press, 2025)
The aim of this research is to analyze the influence of science learning using the cooperative model Group Investigation type assisted by multimedia learning on analytical thinking, evaluation and creative abilities. The type of research used is quasi-experimental research using a pretest-posttest control group design. The type of data used is quantitative data using question instruments and expert validation sheets. Based on the research results, it was found that the application of science learning using the Group Investigation model assisted by learning multimedia had a significant effect on analytical cognitive thinking skills. This is shown by the average posttest ability to think analytical in the control class of 77. Meanwhile, the average posttest result for the experimental class is 94. The application of science learning using the Group Investigation model assisted by multimedia learning has a significant effect on cognitive thinking skills evaluation. This is shown by the average posttest ability to think evaluation in the control class of 73. Meanwhile, the average posttest result for the experimental class is 90. The application of science learning using the Group Investigation model assisted by multimedia learning has a significant effect on the ability to think cognitively and creatively. This is shown by the average posttest ability to think creatively in the control class of 73. Meanwhile, the average posttest result for the experimental class is 90.